PENGARUH KOMPLEKSITAS OPERASI, AUDIT TENURE, UMUR PERUSAHAAN DAN PROFITABILITAS TERHADAP AUDIT DELAY DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (Studi pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Ningrum, Fitri Setya; Hizazi, Achmad; Olimsar, Fredy (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the influence of operational complexity, audit tenure, company age, and profitability on audit delay with Good Corporate Governance (GCG) as a moderating variable in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. This research employs a quantitative approach using purposive sampling, involving 40 companies over three years, resulting in 120 observations. The data analysis method used is multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that company age and profitability have a significant negative effect on audit delay, while operational complexity and audit tenure have no significant effect. Furthermore, Good Corporate Governance is proven to moderate the effect of audit tenure on audit delay, but does not moderate the effects of operational complexity, company age, and profitability on audit delay. This research is expected to contribute to companies, auditors, and investors in understanding the factors that influence the timeliness of financial reporting. Keywords: Operational Complexity, Audit Tenure, Company Age, Profitability, Audit Delay, Good Corporate Governance.